Physiological effects of land and water treadmill exercise in dogs - Fernandes,Mayara Marques Pereira (2022)
ABSTRACT: The application of hydrotherapy is growing in the field of animal rehabilitation to improve strength, endurance, fitness, and range of motion, in addition to reducing pain. In the same way, land-based activity is recommended for various conditions, including hypertension, muscle atrophy, and obesity. There is a lack of studies that evaluate the safety of incremental exercise in American Pit Bull Terriers. This study assessed the influence of activity on underwater and dry land treadmills on the physiological parameters of dogs. In this regard, 12 adult, male, healthy, and untrained American Pit Bull Terriers were subjected to an incremental exercise test (IET) on the underwater treadmill (Group I) and the dry land treadmill (Group II). Heart rate (HR), respiratory rate (RR), rectal temperature (RT), systolic blood pressure (SBP), and electrocardiographic evaluation, were evaluated before activity (T0), immediately after (T1), 30 min after (T2), and 90 min after the end of exercise (T3), and plasmatic lactate concentrations were measured at T0, T1, and T2 time points. Results obtained were submitted to the Shapiro-Wilk test, ANOVA and Tukey’s test, considering P<0.05. Water activity induced a reduction in RR (P=0.00674) in all examinations after the test on the underwater treadmill and proved to be more demanding than activity on the land treadmill, considering the presence of a deeper and slower RR. Exercise sessions in both groups did not elevate the lactate concentration. The IET can be performed safely on an underwater or dry land treadmill in healthy American Pit Bulls.